Scholarly Communication: Making Malaysian Research Available Through Electronic Journal Publishing - Zainab, Awang Ngah; Abrizah, Abdullah (2007)
Most academics adopt a common pattern of dissemination behaviour to communicate their research findings beginning with a preliminary communication to a closed audience within one’s own institution and peaking to submission to a journal for publication. If scholars are the lifeblood of academic publications then the journal system forms the arteries that make possible scientific activities to flow and flourish. Publishing in journals allow academics to niche on an area of research, staking a claim for being the first, propagating and expanding current knowledge in whatever fields. Even though it is estimated that there are over 200 scholarly journals published in Malaysia, only a third are indexed by the international indexing agencies or databases as a result of various shortcomings. This means that local researches are less “available”. Going electronic is one possible solution to making Malaysian contributions more “available” to the global educational community. The paper reports on the various models adopted by e-journal publishers and focusing on the delivery model used by an e-journal hosting system, EJUM (electronic Journal of the University of Malaya), which currently publishes three e-journals gratis, one of which is the Malaysian Journal of Library and Information Science. The paper also reports on the problems faced in enticing local academic journal publishers to be involved in electronic publishing. The numbers and category of users accessing the journals in EJUM is on an increase indicating that the main objective in making Malaysian journals more accessible to the academic community have been met.